PENGARUH MODEL PEMBELAJARAN APTITUDE TREATMENT INTERACTION TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA KELAS VIII SMP NEGERI 15 SAROLANGUN - Rais, Hidayati (STKIP YPM Bangko, 2016)
This study aims to find out and describe the mathematical critical thinking abilities of students taught using the Aptitude learning model. Treatment Interaction is better than using conventional learning in class VIII students of SMP N 15 Sarolangun in the 2015/2016 school year. This study uses a quantitative approach to the experimental method with the posttest Only control group design research design. The population used in this study were students of class VIII A totaling 25 students, class VIII B which amounted to 25 students and class VIII C which amounted to 24 students, where this study was in Sarolangun Middle School 15 15 2015/2016 academic year. The sampling technique used was simple random sampling technique. Data collection techniques in the study used a descriptive test of mathematical critical thinking skills which amounted to 5 items. Data analysis in hypothesis testing using t-test to see where this hypothesis reads hypothesis ift> ttable so Ha is received and H0 is rejected with significance level of 0.05. From the analysis of the latest data in the experimental class obtained an average value of 69.12 while the control class obtained an average of 59.16. Then analyzed using the t-test, the results of hypothesis testing obtained tcount = 2,341 and ttable 1,677. Because tcount > ttable then H0 isrejected and Ha is accepted. So that it can describe the students' critical thinking skills mathematically taught with Aptitude learning model Treatment Interaction is better than those taught with conventional learning class VIII students of SMP Negeri 15 Sarolangun in 2015 2016